DEMOCRATIC ISSUES AS THE BASIS OF MODERN-CONTEMPORARY THOUGHT IN ISLAM - Mursyidan, Auzan; Azhima, A. Izza; Ismail, Salman (Yayasan Maslahatul Ummah Ilal Jannah, 2023)
Democracy is an important part of political history in the world, successfully penetrating the political cultural base of each region from Europe, America, to Asia, in the history of its development democracy has touched many historical events that occurred in the scope of global politics and continues to provide and spread its wings of influence until now, which eventually gave birth to contemporary issues. The existence of democracy even touches Islam, Islamic political systems, Islamic countries, and all Islamic societies around the world. This of course invites a lot of attention from political observers, academics, activists, and religious leaders who study current issues and the influence of the democratic system. This paper will focus on the relationship between democracy as a political regime and Islam as well as its issues as the basis of contemporary Islamic thought with the research method of literature review and data analysis as well as a deeper examination of the references obtained